Osteoporosis - "a silent killer". A review of the current literature from clinician and physiotherapist perspective - Janusz Kocjan (Kazimierz Wielki University, 2015)
Kocjan Janusz. Osteoporosis - "a silent killer". A review of the current literature from clinician and physiotherapist perspective. Journal of Education, Health and Sport. 2015;5(7):63-70. ISSN 2391-8306. DOI 10.5281/zenodo.19173 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A63-70 https://pbn.nauka.gov.pl/works/576516 http://dx.doi.org/10.5281/zenodo.19173 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015.   OSTEOPOROSIS - "A SILENT KILLER". A REVIEW OF THE CURRENT LITERATURE FROM CLINICIAN AND PHYSIOTHERAPIST PERSPECTIVE   JANUSZ KOCJAN   Medical University of Silesia, Faculty of Medicine, Katowice, Poland     SUMMARY             Osteoporosis is a disease characterized by low bone mass and deterioration of bone structure that causes bone fragility and increases the risk of fracture. Individuals with osteoporosis are at high risk of suffering one or more fractures, which are often physically debilitating and can potentially lead to a downward spiral in physical and mental health. Article attempts to discuss this issue from the clinical and rehabilitation perspective. Following contents were included: diagnosis, types of osteoporosis, epidemiology, burden of osteoporosis, types of fractures, treatment and rehabilitation of osteoporosis.   Key words: osteoporosis, porous bone, low bone mass, silent disease.